The Effect of Humic Acid and Silicic Acid on P Adsorption by Amorphous Minerals - Hanudin, Eko (Elsevier, ScienceDirect, 2014)
Andisol is a soil with high P adsorption, this is due to high content in reactive amorphous materials. The present study was conducted to compare humic acid and silicate acid in blocking the P adsorption on amorphous minerals. The results indicated that the old and young formation of parent materials were not different in reactivity of the amorphous minerals and able to adsorb P > 98 % and fit with the Freundlich equation. Application of humic acid and silicate acid with rate of 100 mg/l, respectively, was not effective in decreasing P adsorption. However, silicate acid was a little bit better than humic acid in decreasing P adsorption, in case of pH 4 either pH 6. Infrared spectral characteristics of the amorphous material indicated that the absorption bands of the first region appeared at a range of 3440-3510 cm-1, the band due to stretching vibration of hydroxyl (OH) groups either as structural OH or as adsorbed water. The absorption bands of HOH from adsorbed water appeared ranging from 1639-1655 cm-1. The maximum adsorption bands were observed appeared ranging from 910-972 cm-1, the bands are due stretching vibration of Si-O-Al for allophane with low Si/Al ratio, whereas allophane with high Si/Al ratio appeared at 1033 - 1030 cm-1. In general, the addition of humic acid and silicate acid caused the peak OH, Si-O-Al and Si-O adsorption move to the right and increase the adsorption intensity.